Is Regionalism Competing Against Multilateralism? European and Asian Regional Integration in a Multilateral World - Fouquin, Michel (Eurostudia, 2007)
AbstractThis article compares regional integration in Europe and Asia and asks for its consequences for multilateral negotiation. First it portrays the present situation in Asia before reminding some major features of the European experience. The main thesis of the article is that we are living in a period of enhanced regionalization. If Europe and the US want to show their ability to deal with the concomitant problems, they have to allow developing countries an equal participation in the determination of the rules and terms of international trade.